Seroprevalencia de anticuerpos para Citomegalovirus, Toxoplasma gondii virus de hepatitis A y B en el niño desnutrido grave - de Villarroel Monserrat; Granados Adalberto; Andrade Robert; Méndez Esperanza; Rivero Marilis; Porto Leticia; Callejas Diana; Amesty de Valbuena Alis (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
ABSTRACT: During the last two decades, a number of research studies have boarded the matter of Child Malnutrition trying to understand and explain all of the changes that have occurred as consequence of the reduction of proteic-calorical intake. Today we know of the changes occurring in the immunity system and day by day more research is made on new matters in this field. Anyhow, little is known of the response of the malnourished when exposed to some infectious diseases such as those produced by Citomegalovirus (CMV), Hepatitis virus types A and B and Toxoplasma. In the object of acknowledging this aspect a serological study was performed to investigate the antibodies directed against Hepatitis virus types A and B, CMV and Toxoplasma gondii in a population of 64 gravely malnourished children between 6 and 24 months of age comparing these with a group of 35 similarly aged (eutrophic) children which made up the control group. CMV seroprevalence was 48.4% in the malnourished children group in comparison to 34,2% in the control group. Likewise, Toxoplasma gondii seroprevalence percentage was higher in the malnourished group (10.9%) than in the in the control group (2,8%). No differences were encountered in Hepatitis virus type A seroprevalence between the malnourished group and control group, whilst only one malnourished individual showed IgM positive anticore antibodies (indicators of a recent infection) and none appeared in the control group. When studying recent infection through the investigation of lgM specific antibodies it was found that for CMV, 22% of the malnourished patients had been recently infected in comparison to 8.3% of the control group. Recent toxoplasmosis infection was evidenced in 57.1% of the cases, none of these occurring within the control group. Recent Hepatitis virus type A infection was not observed in any of the two groups. The major percentage of recently infected patients for Toxoplasma gondii and CMV were in the 12 to 24-month age group. These results bring us to the conclusion that malnutrition is a predisposing factor for early CMV and Toxoplasma gondii infection; that these infections are predominantly acquired after the first year of life; and that due to the transitory immunodeficient conditions existent in the malnourished, these infections must be taken into account when encountering clinical symptomatology such as pneumonia, meningoencephalitis or diarrhea which have not been clearly diagnosed by conventional assays. RESUMEN: La desnutrición infantil ha sido motivo de numerosas investigaciones desde hace más de dos décadas tratando de entender y explicar todos los cambios que se suceden como consecuencia de la disminución de la ingesta proteico-calórica. Hoy se conocen los cambios que ocurren en el sistema inmunitario y día a día se investiga más sobre nuevos aspectos en este campo. Sin embargo, poco se conoce sobre la respuesta del desnutrido frente a algunas enfermedades infecciosas como las producidas por el Citomegalovirus (CMV), la Hepatitis por Virus A y B y la toxoplasmosis. Con la finalidad de conocer este aspecto se realizó un estudio serológico para investigar los anticuerpos dirigidos contra el virus de Hepatitis A y B, el CMV y Toxoplasma gondii en una población de 64 desnutridos graves entre 6 y 24 meses y compararlos con un grupo etario similar de 35 niños controles (eutróficos). Se encontró que para CMV la seroprevalencia en el niño desnutrido fue del 48.4% en comparación con el 34,22% del grupo de niños controles. Igualmente, para Toxoplasma gondii el porcentaje de seroprevalencia para el desnutrido (10,9%) fue superior al del grupo control (2,8%). No se encontró diferencias en la seroprevalencia para el virus de Hepatitis A en el grupo de desnutridos y control, mientras que para el virus de Hepatitis B tan sólo un desnutrido presentó anticuerpos anticore IgM positivo (indicativo de infección reciente) y ninguno del grupo control. Al estudiar la infección reciente para CMV mediante la investigación de anticuerpos lgM específicos, se encontró que el 22% de los pacientes desnutridos fueron recién infectados contrastando con el 8,3% del grupo control. Para Toxoplasmosis se demostró infección reciente en el 57.1% de los casos y no hubo ningún caso en el grupo control. No se demostró infección reciente en ninguno de los dos grupos para el Virus de Hepatitis A. El mayor porcentaje de todos los pacientes recién infectados tanto para Toxoplasma gondii como para CMV correspondió al grupo etario de 12 a 24 meses. Estos resultados nos permiten concluir que la desnutrición es un factor predisponente para la infección temprana por CMV y Toxoplama gondii, que ésta se adquiere predominantemente después del año de vida y que dadas las condiciones de inmunodeficiencia transitoria que presenta el desnutrido, deben considerarse estas infecciones cuando existan cuadros clínicos como neumonía, meningoencefalitis o diarrea cuya etiología por los exámenes convencionales no haya podido ser esclarecida.